Role of microRNAs in the regulation of cardiovascular diseases : focus on remodelling - Almeida, Ana G. (2019)
MicroRNAs (miRNAs) are a large class of noncoding RNAs that regulate the expression of protein-coding genes at the post-transcriptional level . They are recognized as regulators of biological processes underlying cardiovascular disorders including hypertrophy, ischemic heart disease, valvular disease and arrhythmias. Particularly, circulating miRNAs are promising biomarkers of cardiovascular pathology (1). MiRNAs are small, noncoding, RNA molecules with approximately 22 nucleotides in length, which act as post-transcriptional regulators of gene expression. Individual miRNAs have been demonstrated to negatively regulate the expression of multiple gene transcripts by the cleavage or suppression of translation of a target mRNA. Conversely, the expression of individual genes can be regulated by multiple miRNAs. Since their experimental description in 1993 (2), a large number of miRNAs known by their gene-regulatory roles in different biological processes, have been catalogued. In fact, miRNAs are known to regulate approximately one third of all coding gene transcripts in mammals, showing their importance as key process modulators (3). Regarding cardiovascular diseases, miRNAs have been identified as key regulators of complex biological processes linked to several conditions as presented above, including left ventricular remodelling, atherosclerosis and myocardial infarction, heart failure, hypertension and arrhythmias (1). miRNAs are expressed in the cardiovascular system, but their role in cardiovascular diseases has not yet been entirely clarified. Moreover, since the discovery that miRNAs are present in the circulation, they have been investigated as novel biomarker as presented bellow. Only 3% of the human genome codes for proteins. Nevertheless, while noncoding RNAs will not act for coding into proteins they modulate all genomic functions. These noncoding RNAs include short miRNAs with approximately 22 nucleotides) and longer, with >200 nucleotides, long noncoding RNAs (lncRNAs) with important biological functions (4) since they are now clearly recognised to play key roles in gene regulation and may simultaneously represent diagnostic and prognostic biomarkers in cardiovascular diseases. (5,6) there are in excess of 2000 human miRNAs (catalogued in mirBase (http://www.mirbase.org) (7). Of note, the key feature of the mechanism of action of miRNAs is that a single miRNA can regulate the expression of several genes, depending on the specificity of the target sequence. On the other side, individual genes can be regulated by different miRNAs particularly if they involve complementary sequences for more than one miRNA. These factors lead to a highly complex regulatory mechanism, often difficult to understand. (8,9). In the healthy adult heart, data from a large sequencing project and other sequential studies, has identified a number of miRNAs that are highly expressed in healthy cardiac tissue and thus expected to play a key role in both normal cardiac function and disease. (10,11) These include miR-1, miR-16, miR-27b, miR-30d, miR-126, miR-133, miR-143, miR-208 and the let-7 family. However, many others have been identified and are now under study. The concept of miRNA-based therapeutics has been emerging and under development, with synthetic antagonists of miRNAs (antagomiRs or antimirs) and very promising in animal models but awaiting new advances in phase II human trials, still in its infancy (12,13). miRNAs clearly intervene in physiological and pathological processes in the cardiovascular diseases. We will review miRNA biology and its role on LV remodeling in myocardial infarction, heart failure, hypertension and aortic stenosis as additionally a note will be provided on the potential of miRNAs for therapeutics.